Development of an electronic student worksheet using local orchid potential to improve critical thinking and collaboration skills in biotechnology learning - Annisa Ul Furqhoni; Ixora Sartika Mercuriani (JURNAL BIOEDUKATIKA, 2025)
This study aims to develop an electronic (e)-student worksheet  integrated with the Project-Based Learning (PjBL) model and to enhance the critical thinking and collaboration skills of Grade X high school students in biotechnology learning based on the local potential of the Nglanggeran Ancient Volcano Orchid. Employing a Research and Development (R and D) approach, the research used the ADDIE model consisting of Analysis, Design, Development, Implementation, and Evaluation in the product development process. The e-student worksheet was created digitally using Canva and included multimedia elements to increase student engagement. The study involved a limited trial with 15 students and a field trial with 70 students divided into experimental and control groups. Data collection methods included interviews, questionnaires, and pretest-posttest essay-based assessments. Instrument validation showed all items were valid and reliable, with a Cronbach’s Alpha score of 0.843. The results revealed moderate improvement in students’ critical thinking skills with an N gain of 0.67 and collaboration skills with an N gain of 0.61 in the experimental group. These findings indicate that the experimental group outperformed the control group, validating that the contextualized PjBL approach effectively facilitates deeper cognitive processing and reinforces interpersonal skills compared to conventional methods. Statistical analysis using MANOVA confirmed significant differences between the two groups with Wilks’ Lambda value of 0.006 and p value less than 0.001. Expert and user feedback indicated the product was practical, accessible, and contextually relevant.